Bend sensor arrays for hand movement tracking in biomedical systems - Saggio, G. (2011 4th IEEE International Workshop on Advances in Sensors and Interfaces, 2011)
Bend sensor's electrical feature and mechanical pliability allow to easily realize a cost effective and reliable system to measure human postures. With this kind of sensors we realized a data glove capable to accurately measure all degree of freedom of a human hand. In particular, in collaboration with the Flexpoint Sensor Systems Inc., we designed and realized a unique device capable to measure at the same time the flex-extension movements of the three joints of one finger. Experimental results demonstrated good performances obtained in terms of accuracy and repeatability of the measures.